2001
DOI: 10.1074/jbc.m100878200
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Alkyl Phospholipids Are Specific, High Affinity Peroxisome Proliferator-activated Receptor γ Ligands and Agonists

Abstract: Synthetic high affinity peroxisome proliferator-activated receptor (PPAR) agonists are known, but biologic ligands are of low affinity. Oxidized low density lipoprotein (oxLDL) is inflammatory and signals through PPARs. We showed, by phospholipase A 1 digestion, that PPAR␥ agonists in oxLDL arise from the small pool of alkyl phosphatidylcholines in LDL. We identified an abundant oxidatively fragmented alkyl phospholipid in oxLDL, hexadecyl azelaoyl phosphatidylcholine (azPC), as a high affinity ligand and agon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
198
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 253 publications
(212 citation statements)
references
References 53 publications
(32 reference statements)
11
198
0
3
Order By: Relevance
“…This was first demonstrated by Davies et al 58 , who demonstrated that non-enzymatically oxidized alkyl phospholipids present in oxidized low density lipoproteins (LDL), are high affinity ligands for PPARγ. One of these species was identified as 1-hexadecyl-2-azelaoyl phosphatidylcholine (azPC), which had a Kd for binding to the PPARγ receptor of approx.…”
Section: Evidence That Oxidized Gpc Are Native Pparγ Ligandsmentioning
confidence: 92%
See 4 more Smart Citations
“…This was first demonstrated by Davies et al 58 , who demonstrated that non-enzymatically oxidized alkyl phospholipids present in oxidized low density lipoproteins (LDL), are high affinity ligands for PPARγ. One of these species was identified as 1-hexadecyl-2-azelaoyl phosphatidylcholine (azPC), which had a Kd for binding to the PPARγ receptor of approx.…”
Section: Evidence That Oxidized Gpc Are Native Pparγ Ligandsmentioning
confidence: 92%
“…One of these species was identified as 1-hexadecyl-2-azelaoyl phosphatidylcholine (azPC), which had a Kd for binding to the PPARγ receptor of approx. 40 nM 58 .…”
Section: Evidence That Oxidized Gpc Are Native Pparγ Ligandsmentioning
confidence: 99%
See 3 more Smart Citations